Exploring the virulence potential of Staphylococcus aureus CC121 and CC152 lineages related to paediatric community-acquired bacteraemia in Manhiça, Mozambique - Garrine, Marcelino (2024)
Funding Information: This study was supported by Funda\u00E7\u00E3o para a Ci\u00EAncia e a Tecnologia (FCT, Portugal) through funds to GHTM\u2014UID/04413/2020, LA-REAL\u2014LA/P/0117/2020 and to the Project DREBI, Ref. 2022.07931.PTDC ( https://doi.org/10.54499/2022.07931.PTDC ). CISM receives core funding from \u201CAgencia Espa\u00F1ola de Cooperacion Internacional para el Desarollo (AECID)\u201D. MG was supported by grant 145278, from Funda\u00E7\u00E3o Calouste Gulbenkian \u201CCalouste Gulbenkian Foundation, Portugal\u201D. MA was supported by grant UI/BD/154472/2022 and JN by grant 2022.07931.PTDC from FCT, Portugal. SSC was supported by FCT through CEECINST/00042/2021/CP1773/CT0009 ( https://doi.org/10.54499/CEECINST/00042/2021/CP1773/CT0009 ). Publisher Copyright: © The Author(s) 2024.